Brands across the Mekong: a dual case history - Andrews, Tim (Henry Stewart Talks, 2009)
Environmental backdrop: the greater Mekong sub-region, Lao market entry: Unilever and Castrol, Product and pricing, Promotion sensitivities: Lao versus Thailand, Promotion strategies, Distribution challenges